2012
DOI: 10.1590/s0004-27492012000500009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and causes of blindness in an urban area of Paraguay

Abstract: Purpose: To determine the prevalence and causes of blindness in Piribebuy, Paraguay. Methods: A population based study was conducted from September to November 2007 in Piribebuy, Paraguay. Based on the city map, seven clusters were randomly selected, containing 22 to 36 squares (423 to 578 houses) each, where all subjects ≥ 40 years old who agreed to participate were included in the study. Presenting vision acuity (VA) was obtained for each eye, with 'E' Snellen charts 6 meters far from the patient with approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The prevalence of the causes of blindness in Paraguay, was evaluated in an epidemiological study conducted by Paraguayan institutions in collaboration with authors from U.S. institutions and from the International Agency for Prevention of Blindness (IAPB) (5) . The authors found a lower prevalence of visual impairment in relation the only previous population-based study from the same country, in 2003 (6) .…”
Section: Wallace Chamonmentioning
confidence: 99%
“…The prevalence of the causes of blindness in Paraguay, was evaluated in an epidemiological study conducted by Paraguayan institutions in collaboration with authors from U.S. institutions and from the International Agency for Prevention of Blindness (IAPB) (5) . The authors found a lower prevalence of visual impairment in relation the only previous population-based study from the same country, in 2003 (6) .…”
Section: Wallace Chamonmentioning
confidence: 99%
“…Other important accomplishment of VISION 2020 Latin America is a push for evidence-based medicine to guide national policies and programs on eye care (5) , such as some Rapid Assessment of Avoidable Blindness (RAAB) studies performed in the last three years (8) . New ideas aimed at the current VISION 2020 Latin America challenges should be carried through in most regional countries, especially those based on the development and continuous maintenance of technical local teams or subcommittees acting as manager of eye care activities as well as the achievement of funding resources to keep members engaged and productive.…”
mentioning
confidence: 99%